2020
DOI: 10.1101/2020.04.29.067561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Durable memories and efficient neural coding through mnemonic training using the method of loci

Abstract: Mnemonic techniques, such as the method of loci, can powerfully boost memory. Here, we compared memory athletes ranked among the world's top 50 in memory sports to mnemonics-naïve controls. In a second study, participants completed a six-weeks memory training, working memory training, or no intervention. Behaviorally, memory training enhanced durable, longer-lasting memories. fMRI during encoding and recognition revealed task-based activation decreases in lateral prefrontal, as well as in parahippocampal and r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Yet, mnemonic strategies are underutilized in psychology and cognitive neuroscience of memory and could in particular inform recent debates about the role of long-term memory structures in working memory processes. For example, in line with the WMEM conjecture that episodic context representations are information-theoretically cheap to maintain (Beukers et al, 2021), we recently observed that both memory champions and mnemonically trained novices exhibit very efficient neural coding when applying mnemonic strategies to memory tasks, with decreases in brain activation and neural representational similarity in the lateral prefrontal cortex (Wagner et al, 2021). Also Miller et al (2022) in their new study observed a significant decrease in lateral prefrontal activity during WM encoding across training, suggesting similar enhancement of encoding efficiency.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Yet, mnemonic strategies are underutilized in psychology and cognitive neuroscience of memory and could in particular inform recent debates about the role of long-term memory structures in working memory processes. For example, in line with the WMEM conjecture that episodic context representations are information-theoretically cheap to maintain (Beukers et al, 2021), we recently observed that both memory champions and mnemonically trained novices exhibit very efficient neural coding when applying mnemonic strategies to memory tasks, with decreases in brain activation and neural representational similarity in the lateral prefrontal cortex (Wagner et al, 2021). Also Miller et al (2022) in their new study observed a significant decrease in lateral prefrontal activity during WM encoding across training, suggesting similar enhancement of encoding efficiency.…”
supporting
confidence: 62%
“…Consistent with both the LTWM and WMEM models, but not with any account of only short-lasting changes underlying activity-silent working memory, memory athletes and mnemonically trained novices can not only memorize more information, but also contain it for longer than untrained control subjects (Wagner et al, 2021). Even if not intentionally utilized in experimental designs, the possibility of study material being encoded by mnemonic strategies should be considered carefully, as in our experience it can be difficult to exclude mnemonic strategies from (both long-term and working) memory tasks, and a considerable amount of the observed performance variance might actually be driven by habitual differences in the intuitive or explicit use of mnemonic strategies.…”
mentioning
confidence: 68%
“…We speculate that accurate performance might go hand-inhand with neuronally efficient processing 79 , which would be indexed by lower entorhinal grid magnitudes and a reduced need to employ additional co-activation of and connectivity with other brain regions. To provide an example, memory training was shown to decrease brain activity during memory processing while increasing performance 80 . Individual inability to accurately memorize and re-trace paths might thus be coupled to higher grid-like signals as there was increased need for support through the cognitive map provided by the entorhinal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that accurate performance might go hand-in-hand with neuronally efficient processing (Neubauer and Fink, 2009), which would be indexed by lower entorhinal grid magnitudes and a reduced need to employ additional co-activation of and connectivity with other brain regions. To provide an example, memory training was shown to decrease brain activity during memory processing while increasing performance (Wagner et al, 2021). Individual inability to accurately memorize and re-trace paths might thus be coupled to higher grid-like signals as there was increased need for support through the cognitive map provided by the entorhinal cortex.…”
Section: Discussionmentioning
confidence: 99%